(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Accounting creativity is the process of changing financial information beyond the limits of accounting norms to provide an improved overview of a company’s financial status and performance. The current study investigates creative accounting practices in Pakistan, focusing on auditors’ competency, integrity, independence, and ethics in detecting creative accounting practices, thereby enhancing financial transparency in the business context. The data for the study were collected via a questionnaire using a Google Web form shared with 120 auditors from audit organizations working in Pakistan. The results of multiple regression analysis revealed that auditor competency, honesty, independence, and ethics have a significant influence on detecting creative accounting practices followed by accountants to manipulate the financial position and performance of their organizations. The results of this study hold significant practical implications for auditors, regulators (such as the SECP), and policymakers. Future research may be focused on assessing the efficacy of audit committees in overseeing companies’ stakeholder reporting and their management of ethical and sustainability concerns. This study contributes to the literature by exploring the realm of accounting creativity in Pakistan, specifically delving into auditors’ capabilities and integrity in identifying creative accounting practices. It sheds light on the significance of auditors’ competency, honesty, and ethical considerations in uncovering manipulative financial reporting strategies employed by accountants.